Ekstrak Etanol Kulit Buah Manggis Sebagai Masker Gel Peel-Off Berantioksidan - Priyanti Priyanti; Tri Partuti; Nusaibah Nur Amalina; Desy Rahmiaty; Wulandari Fera Yanti; Hutssy Elya Nadyana; Alika Arum Daniya; Nurul Annisa; Azza Hanif Harisna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
Peel off gel masks have become a trend in the field of beauty as a facial skin care. Utilization of mangosteen rind extract is thought to be able to provide more function on the mask as its high levels of antioxidant. This study discusses the optimum formulation of antioxidant peel off gel mask with mangosteen rind ethanol extract. Mangosteen rind was obtained from the market in the South Tangerang area and then extracted using 96% ethanol as the solvent by maceration. Peel off gel mask preparation is formulated with extract concentrations of 1%, 2% and 4%. Stability test in the form of analysis of pH, viscosity, dry time, and homogenation was carried out for four weeks. Antioxidant analysis was carried out to detect flavonoid, saponins and tannins. The results showed that the extract contained flavonoids, saponins and tannins with free radical scavenging values ​​of 16.10%. The optimum formulation of peel off gel mask is with 2% extract because it has an acidic pH, a viscosity value of 8025 cps, a thick texture, and has a drying time of about 14 minutes.